Experimental study on structural responses of fibre glass plates under lateral moving. (3rd October 2019) - Wulff, M.; Quinton, B. W. T.; Ehlers, S.
ABSTRACT: Experiments and numerical simulations of moving (sliding) loads on steel grillage structures have demonstrated a significant difference in plastic capacity when subject to moving loads versus stationary loads. If a moving load induces plastic deformation, a grillage structure's plastic capacity can be dramatically less; even if the load is otherwise tolerable as a stationary load. For fibre reinforced plastic materials, which are commonly used in lifeboat hulls, any effects due to moving (sliding) loads are widely unknown. This paper presents selected results from laboratory moving (sliding) load tests on fibre glass plates using a moving load apparatus. The results identify an increase of damaged plies due to the effects of moving loads at high deformations, compared to similar stationary loads. It was further observed that moving loads can lead to a fracture of the hull at lower forces or deflections in comparison with stationary loads.